Pengaruh Problem Based Learning terhadap Hasil Belajar Fiqih Thaharah Siswa MTsN 2 Surakarta - Muti'ah Nuha Mumtazah; Dwi Ambarwati (Al-Khazin: Jurnal Pendidikan Agama Islam, 2026)
This study is motivated by the low student learning outcomes in Fiqh, particularly in the topic of Thaharah, which is caused by the use of conventional teaching methods that lack student engagement. This study aims to determine the effect of the Problem Based Learning (PBL) model on the learning outcomes of seventh-grade students at MTsN 2 Surakarta. This research employs a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The research subjects consisted of 48 students divided into an experimental class and a control class. Data were collected through tests, interviews, and documentation, with instruments in the form of multiple-choice questions that had been tested for validity and reliability. Data analysis was conducted using normality tests and t-tests to examine the hypothesis. The results indicate a significant difference between the learning outcomes of the experimental and control classes, with the experimental class achieving higher scores. This finding demonstrates that the Problem Based Learning model is effective in improving Fiqh learning outcomes. Therefore, PBL can be used as an innovative learning alternative to enhance student engagement and understanding.